Oxidative status and fertility of ewes supplemented coffee pulp during estrous synchronization and early pregnancy - Salinas-Rios, Teodulo; Sánchez-Torres-Esqueda, María Teresa; Díaz-Cruz, Antonio; Cordero-Mora, José Luis; Cárdenas León, Mario; Hernández-Bautista, Jorge; Nava-Cuellar, Cuauhtémoc; Nieto Aquino, Rafael (Revista Colombiana de Ciencias Pecuarias, 2016)
it is known that coffee pulp can modify the oxidative status and fertility in dairy cows. Objective: to evaluate the effect of dietary supplementation with coffee pulp on the antioxidant capacity, lipid oxidation and reproductive characteristics of ewes during estrous synchronization and early gestation. Methods: forty Dorset-Suffolk crossbred ewes with 3 or 4 parturitions were allocated to two treatments: T0 (n = 21), ewes supplemented with 450 g of a control feed; and T1 (n = 19), ewes supplemented with 450 g of the feed with 25% coffee pulp. Supplementation began 14 days before estrous synchronization and ended 25 days after breeding. During estrous synchronization, progestogen (CIDR, Controlled Internal Drug Release) was inserted and left in situ for 11 days. Eighteen hours later, estrous detection began with the aid of rams. Blood samples were collected at different times of synchronization and during early pregnancy to determine antioxidant capacity, lipid oxidation and blood progesterone concentration. Pregnancy diagnosis was performed 30 and 60 days after CIDR removal. Results: supplementation with coffee pulp did not affect estrous onset, estrous response or progesterone concentration, but fertility decreased from 100 to 78.95%. The antioxidant capacity measured using the FRAP technique was greater in coffee pulp supplemented ewes only before progestogen insertion. Coffee pulp did not modify lipid oxidation; however, this variable was affected by sampling time, decreasing after progestogen removal to its lowest values at 22 days into pregnancy. Conclusion: although supplementation with coffee pulp at 25% in the concentrate increased antioxidant capacity of ewes before insertion of progestogen, it is not recommended to use this percentage during synchronization or early pregnancy since it can negatively affect gestation rate.